The despised and the damned; the Russian peasant through the ages. - Koslow, Jules, 1916- (Russia old and new series, 1972)
Examines the history and way of life of the Russian peasant past and present including discussions of serfdom, the new relationship of peasant to state, and the effect of collective and state farms.